Climate Change Vulnerabilities of Woman in Bangladesh (The Agriculturists, 2017)
This paper reviews the existing literature on gender differentiated climate change vulnerabilities in developing countries including Bangladesh. It is evident that climate change amplifies the vulnerabilities of poor people who are marginalized and more dependent on the threatened natural resources. Among the poor people women are seemed to be disproportionately affected by climate change. The review took utmost effort to unfold the root causes of gender differentiation under climate change scenario. It identifies some governing factors such as ownership, political affiliation, labor force participation that determine the extent of the effect of climate change. Deeper analyses of the literatures indicate that gender differentiated impacts- are directly related to traditional gender roles of women. It also reveals the constraints to womens adaptation resulting from access to resource allocation and other elements of society. Drawing lessons from the existing literatures, finally it outlines some of the policy options to ensure the inclusion of women in development arena.The Agriculturists 2016; 14(2) 113-123